Atypical presentation of disseminated tuberculosis an autopsy case report (Journal of Armed Forces Medical College, Bangladesh, 2015)
Reporting a case of natural death where blind anti-tubercular treatment started late due to atypical presentation and conflicting laboratory reports.The deceased was a 25 year old male Indonesian rubber plantation worker initially diagnosed as Crytococcal infection and had been treated on antifungal regime. Histological examination of various organs after post mortem examinations revealed disseminated tuberculosis. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22936 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014